Model Analisis Niat Menggunakan Pestisida Nabati oleh Petani Cabai di Kabupaten Garut - Pratama, Luthfie Alie; Karyani, Tuti; Setiawan, Iwan (Universitas Galuh, 2026)
Garut is a chili commodity in West Java. However, in recent years, the production of chili in the district has decreased. Chili production in Garut District around 159 thousand tons, or decreased around 13% of production compared to the previous year (BPS, 2025). One of the causes is pest and disease organism (PDO). Recently farmers still rely on chemical pesticides, while have negative impacts on health, ecosystems, environment, and increase PDO resistance. Also, chemical pesticides stated are not in line with the principles of sustainability. The government and penyuluh have also encouraged farmers to adopt integrated pest management (IPM) practices, such as biochemical pesticides, through various policies, extension services, training, and assistance. However, these efforts have not effectively encouraged farmers to adopt biochemical pesticides. Therefore, this study aims to determine and analyze farmer behavior based on the Theory of Planned Behavior (TPB) approach to determine the relationship between attitude, subjective norm, and perceived behavioral control on farmers' intention to use biochemical pesticides. This study used a quantitative verification method, while the data used were primary data from 100 chili farmer respondents in Cikajang District as a representative center chili production in Garut Regency. Data are collected using a stratified random sampling method. The results showed a positive and significant relationship between attitude, subjective norm, and perceived behavioral control on the intention to use biochemical pesticides. The findings of this study indicate the need for interventions that can encourage attitude, subjective norms, and perceived behavioral control to increase the use of plant-based pesticides.